MENINGKATKAN AKTIVITAS BELAJAR DAN PEMAHAMAN SISWA DALAM PEMBELAJARAN STRUKTUR ATOM MELALUI STRATEGI PETA KONSEP DENGAN PENULISAN JURNAL BELAJAR PADA KELAS X-2 SMA NEGERI 2 TANJUNG - Syaiful Arifin (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2014)
Abstract. The concept of atomic structure is one of the chemical concepts are quite abstract and difficult to be understood by high school students. From the results of learning in the school year 2012/2013 in SMAN 2 Tanjung is found that only 35% of the 243 students who are classified as being above the level of mastery learning about atomic structure. Based on these data, it is assumed that to improve activities and understanding of student learning atomic structure. It is expected can change to a better rate through the strategy Concept Mapping with the task of writing Journal of Learning in the atomic structure. The results of research are obtained before use concept mapping acquired the average of value about 65.83. In the first cycle the atomic structure of matter obtained the average value about 70.17. In the second cycle the atomic structure of matter obtained the average of value about 75.50. It represents that increase understanding of student from the average of value about 4.34 in the first cycle, and increase about 5.33 in the second cycle. While the average activities of student learning in the first cycle about 58.66% have increase about 11.34% to 70.00% in the second cycle. Teacher implements the strategy Concept Mapping with the task of writing Journal of Learning in the atomic structure of matter, that is based on constructivism, according the plan that had been developed, so that activities and understanding of student learning atomic structure can be increased on the class X-2 SMAN 2 Tanjung in academic year 2013/2014.Keywords: learning activity, atomic structure, concept mapping, journal of learning.